Identification and Characterization of The Causal Agent of Infected Iceberg Lettuce (Lactuca Sativa L.) in Perak, Malaysia. - Noor Afiza, Badaluddin; Saiful Iskandar, Khalit; Mohammad Hailmi, Sajili (2019)
Lack of knowledge about the causal agent of infected crops lead farmers to use wrong treatment on their crops, which is causing negative effects on environment and human’s health. This study was conducted to identify and characterize the causal agent from the infected iceberg lettuce (Lactuca sativa L.) in Perak, Malaysia. The infected iceberg lettuces were sampling from Perak area and the causal agent was isolated by direct plating technique on a nutrient medium. The isolated bacteria were identified by molecular method and biochemical test. Molecular identification was carried out using 16S rRNA sequence and then, several tests such as amylase, catalase, oxidase and others were done for identification of bacterial species based on their biochemical activities. The obtained results showed that Serratia marcescenes and Stenotrophomonas sp. were identified as the causal agents. The pathogenicity has been confirmed by the establishment of Koch’s Postulate, which showed 100% disease infection on them. The environmental effects also have been tested on the bacteria to study the ability of bacteria to grow in different environmental conditions based on different in pH, salinity, and temperature. All the bacterial sample showed that they able to growth on the pH between 4.0 to 9.0, at the temperature 10 °C to 45 °C and at the addition salinity to the medium between 2.5 %, 5.0% and 7.5 %.